PENGARUH PENERAPAN METODE BERMAIN PERAN TERHADAP KEMAMPUAN BERBICARA PADA ANAK USIA 4-5 TAHUN DI TK AISYIYAH 09 KECAMATAN TENAYAN RAYA PEKANBARU - Nur, Eli Sofia; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine how much influence the application of methods play a role in the ability to speak in children aged 4-5 years in the District 09 kindergarten Aisyiyah Tenayan Raya Pekanbaru. The population and sample of this research is children aged 4-5 years amounted to 12 children. Data collection techniques were used that observation. The data analysis technique used in this study is Wilcoxon Signed Ranks Test. The results were obtained then can researchers conclude that there is a difference in the child's speech is significant between before and after the application of methods play a role. So it means Ho is rejected and Ha accepted which means no difference before and after treatment.Keywords: speech, methods play a role